Hydrogen Evolution Activity of Platinum Nanoparticles Decorated on Silver Nanowire Networks and Graphite Electrodes - Martina Schwager; Felix Deuringer; Michael Moser; Johannes Ostermair; Jenni Richter (Advanced Energy Conversion Materials, 2024)
The catalytic activity of graphite (C) and conductive silver nanowire (AgNW) networks coated on glass and graphite substrates with low platinum content towards hydrogen evolution reaction (HER) is reported. The results exhibit that the chronoamperometric electrodeposition of platinum on AgNW substrates results in the formation of spherically shaped nanoparticle agglomerates aligned on the nanowires. Also, platinum doped graphite electrodes with a rough surface showed an efficient distribution of platinum nanoparticles (PtNPs). Studies of the electrocatalytic HER activity as a function of platinum loading indicate that the optimum loading is in the range of 60 µg/cm2 and further loading results only in a minor reduction of the overpotential. At low Pt content, a synergistic effect of the AgNW network in terms of enhancement of the HER performance was observed. Tafel analysis showed that in the low overpotential region, the Volmer reaction was the rate determining step for the graphite based electrodes. The graphite substrate in conductive connection with the nanowires was shown to significantly boost the hydrogen formation rate.